GeoBlocks: A Game-Based Approach for Teaching Geometry in Primary Education - Maria M. Serrano-Baena; Paula Triviño-Tarradas; Enrique Martínez-Jiménez; Carlos Ruiz-Díaz (International Journal of Serious Games)
This study introduces GeoBlocks, an innovative educational project inspired by the classic Tetris game, aimed at enhancing geometric reasoning and mathematical skills among Primary Education students aged 10 to 12. Conducted over 12 sessions, the project integrates game-based learning with hands-on activities to teach essential geometric concepts, including shape recognition, measurement, and area calculation. Utilizing pentominoes, students engage in constructing and manipulating geometric shapes, fostering both individual and collaborative learning experiences. A descriptive-exploratory study is presented involving university students enrolled in a Geometry Teaching course, who implemented the project and subsequently evaluated its pedagogical effectiveness using a Likert scale survey. Results indicate that GeoBlocks not only actively engages students but also significantly deepens their understanding of Geometry and enhances teamwork and communication skills. Future research should empirically validate these findings with a sample of Primary Education students and explore the long-term impact of GeoBlocks on geometric proficiency and overall academic performance.